Utilization of innovative educational applications for developing the spiritual and creative potential of future educators - Yeshenkulova, Elvira; Arymbayeva, Kulimkhan; Maulenberdieva, Gulzhan; Yeshenkulova, Dinara; Abdigapbarova, Ulzharkyn; Kolesnik, Kristina (International Journal of Evaluation and Research in Education (IJERE), 2025)
Contemporary training of future educators necessitates the development of not only professional but also spiritual and creative qualities. This study aims to evaluate the effectiveness of an online course utilizing a chatbot to enhance the spiritual and creative potential of students in pedagogical disciplines. The research involved 534 of 4thyear students from two universities in Kazakhstan, divided into an experimental group (n=268) and a control group (n=266). The experimental group completed six modules covering creative thinking, spiritual development, public speaking, and other aspects of self-development. Pre- and post-course surveys assessed five indicators of spiritual health: vitality, resilience, values, meaning, and openness to change. The intervention resulted in a significant improvement in three key indicators: resilience, values, and meaning. These enhancements are likely to contribute to better preparation of future educators by strengthening their resilience to professional challenges, helping them understand their values and goals, and enhancing their awareness of the significance of education for society.